Investigating the air and liquid porosity of sea ice - Swait, Hayley (Department of Chemical Engineering, 2025)
Micro-scale sea ice properties have cascading effects onto larger scale climate and ocean systems. Brine and air inclusions are influenced by the growth conditions, which are highly dynamic in the Antarctic Marginal Ice Zone (MIZ) compared to the calmer Arctic. There are varying depths within an Antarctic pancake floe due to these dynamic conditions, yet the spatial variability of brine and air porosity profiles has not been previously investigated. Additionally, the sea ice brine phase is greatly influenced by temperature, yet similarly there are limited studies on the impact of temperature storage and heating methods on brine inclusions. Understanding the impacts of environmental and storage conditions is essential to ensure accurate and representative analysis of sea ice's thermally responsive properties. In this study, non-destructive X-ray computer tomography (CT) analysis was used to investigate the brine and air inclusions within pancake ice from the Antarctic MIZ during winter 2019 and 2022 expeditions. Sampling protocols from the 2019 expedition were optimised during the 2022 expedition to store samples at the CT analysis temperature (-10°C) to minimise the impact of low temperature (-18°C) storage on these inclusions. Investigating the impacts of low temperature storage and heating methods on these inclusions was then conducted through uni- (UD) and multidirectional (MD) heating samples from -18°C to -10°C. This study showed on average reductions of 41% in the brine porosity of sea ice after being subjected to low temperature storage, unlike air porosity that showed no significant changes. However, there was no significant difference between the UD and MD heating methods. The number of brine inclusions increased after low temperature storage. The brine inclusions showed a decrease in sphericity in samples subjected to low temperature storage conditions. Air showed slight increases in the number of air inclusions in the sections in the upper region of the ice while the lower region showed a decrease in air number densities, potentially attributed to the gas saturation factor within the sea ice. In addition to the storage conditions influencing the inclusions, the spatial variability of coring locations within a pancake floe has also shown to have slight variation in the porosity profiles within sea ice samples. This study disqualifies the general assumption that sea ice porosity is not affected by low temperature storage conditions and therefore the storage conditions are of paramount importance in studying the microstructural properties of sea ice. Maintaining sea ice samples at higher analysis temperatures that is closer to in situ temperatures will minimize the effects of low temperature storage on the sea ice inclusions.